Autonomic dysfunction is associated with cardiac remodelling in heart failure patients. (28th September 2017) - Ali, Amna; Holm, Hannes; Molvin, John; Bachus, Erasmus; Tasevska‐Dinevska, Gordana; Fedorowski, Artur; Jujic, Amra; Magnusson, Martin
Abstract: Aims: Orthostatic hypotension (OH) is a cardinal sign of autonomic dysfunction and a common co‐morbidity in heart failure (HF). The role of autonomic dysfunction in the development of structural cardiac anomalies in HF patients has not been sufficiently explored. We aimed to assess relations between orthostatic blood pressure (BP) responses during active standing and echocardiographic changes in a series of patients admitted for HF. Methods and results: One hundred and forty‐nine patients hospitalized for HF [mean age: 74 years; 30% women; ejection fraction (LVEF) 40 ± 16%] were examined with conventional echocardiograms and active‐standing test. Associations of cardiac remodelling parameters with the difference between supine and standing (after 3 min) systolic/diastolic BP were examined. Systolic BP decreased (−1.1 ± 15 mmHg), whereas diastolic BP increased (+1.0 ± 9.5 mmHg) after 3 min of active standing. A total of 34 patients (23%) met conventional OH criteria; i.e. systolic/diastolic BP decreases by ≥20/10 mmHg. In the multivariable linear regression analysis, adjusted for traditional cardiovascular risk factors and LVEF, a decrease in systolic BP upon standing was associated with greater left atrial volume [β per −10 mmHg: 2.37, standard error (SE) = 1.16, P  = 0.043], and greater left ventricular mass (β per −10 mmHg: 5.67, SE = 2.24, P  = 0.012), but not with other echocardiographic parameters. No significant associations were observed between signs of cardiac remodelling and decrease in diastolic BP. Conclusions: Orthostatic decrease in systolic BP among older HF patients is associated with structural cardiac changes such as increased left atrial volume and left ventricular mass, independently of traditional risk factors and left ventricular dysfunction.